Children's Social Skills: A Study of The Process of Shaping Children's Early Social Skills by Parents in Indonesia - Meiti Subardhini; Sakroni Sakroni; Septyan Berliana (Asian Social Work Journal, 2023)
The background that motivates this research is the many highlights that are focused on the attitudes and behaviour of children in particular and adolescents in general who are considered to have low social skills. This research aimed to find out the process of shaping children's social skills from an early age carried out by parents in Bandung City. A quantitative approach with a descriptive method was chosen in the process of conducting the research. The selection of research subjects was carried out using a non-probability method, namely convenience sampling from parents who have school-age children (elementary and junior high school) who live in Bandung. The data collection method is done through a questionnaire in the form of a questionnaire in digital form (Google form) whose results will be processed with descriptive statistical data analysis techniques. The results showed that the dominant respondents with female gender, as many as 101 people (72.14%), male gender as many as 39 people (27.86%) with various levels of age, education, employment and income. The age of the respondent's child is dominant in the range of 5-10 years, namely 72 people (51.43%), and aged 16-20 years the least (4 people (2.86%)). The results of the empathy aspect score show the results of respondents strongly agreeing (77.86%), the participation aspect shows the results of respondents strongly agreeing (60.72%) and the assertive aspect shows the results of respondents agreeing (65%), all three of which are in the moderate category. From this study, it is expected that there is a need for socialisation about the process of forming or teaching in children and adolescents and the role of the environment outside the family in the formation of social skills.